TRANSFORMASI KEDAI TUAK SEBAGAI SARANA PENGINJILAN GEREJA - Siagian, Riris Johanna; Silalahi, Jojor; Saragih, Ratna (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2020)
This writing tries to analyze the influence of kedai tuak toward the presence of congregation members, especially males in church. It begins with a study of the concrete reality of the church dan how the common response of the father according to it. And how the church does evaluation and reflection of the church, by doing persuasive action for serving the laity, not by giving a negative stigma. This research is qualitative with Sociology of Religion perspective. The expectation, the transformation for changing of preaching method will get.